Equity Vesting and Investment - Edmans, Alex; Fang, Vivian W.; Lewellen, Katharina A. (Review of Financial Studies, 2017)
This paper links the CEO's concerns for the current stock price to reductions in real investment. We identify short-term concerns using the amount of stock and options scheduled to vest in a given quarter. Vesting equity is associated with a decline in the growth of research and development and capital expenditure, positive analyst forecast revisions, and positive earnings guidance, within the same quarter. More broadly, by introducing a measure of incentives that is determined by equity grants made several years prior, and thus unlikely driven by current investment opportunities, we provide evidence that CEO contracts affect real decisions.